Biography of self taught men: with an introductory essay - Edwards, B.B. (John Breckinridge library., 1832)
Advertisement. -- Introductory essay. -- Biographical sketches. -- Roger Sherman. -- Professor Heyne. -- Stephen Duck. -- John Jones.--William Whipple.--Eli Whitney.--Alexander Murray.--Stephen Hopkins. -- Professor Lee. -- William Gifford. -- John M'Lean. -- Thomas Baldwin.--David Rittenhouse.--Samuel Huntington.--William Edwards.--Robert Bloomfield.--Thomas Scott.--Lott Cary.--John Opie.--Nathaniel Smith.--John Godfrey von Herder.--Giovanni Battista Belzoni.--Jonas King. -- Isaac Milner. -- William Caxton. -- Richard Baxter. -- Arthur Young.--Humphrey Davy.--Adam Clarke.--Charles G. Haines.--Henry Clay.--Carsten Niebuhr.--James Ferguson.